Establishing good rapport in anesthesiarelated doctor-patient communication: bridging the triangular communication between anesthesiologist-surgeon-patient - Widnyana, IMG; GA Senapathi, Tjokorda; Cindryani, Marilaeta (Bali Journal of Anesthesiology, 2017)
Doctor-patient communication is central in clinical practice. Communication skill has been an essential component of clinical competence to become a five-star doctor. In the other hand, there are major problems in doctor-patient communication that would lead to medical disputes even malpractice suspicions. With effective communication, a definitive theory would turn into high-quality medical practice and improve patient safety and satisfaction to a whole new level. Based on the Calgary-Cambridge observation guide, there is five point plan of tasks that embrace doctor and patient in daily interviews starting from initiating the session, gathering information, building the relationship, explanation, and planning, and closing. Those tasks would have been easily introduced when you are dealing with a good healthy patient. But in anesthesia-related, wide range of patients are met in different settings and conditions